GUIDANCE AND COUNSELING SERVICES FOR CHILDREN WITH SPECIAL NEED IN INCLUSIVE PRIMARY SCHOOLS - Dewi Sri Rejeki; Mahardika Supratiwi; Herry Widyastono; Gunarhadi Hermawan; Joko Yuwono; Leni Ambar Cahyani (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2024)
Children with special needs often face complex challenges beyond their primary disability. These challenges can significantly impact their overall well-being and academic performance. This study aimed to assess the provision of guidance and counseling services for ABK in inclusive primary schools in Surakarta, Indonesia. A survey involving 10 inclusive primary schools was conducted, utilizing questionnaires and semi-structured interviews with teachers and parents. Data analysis employed descriptive analysis of both quantitative and qualitative data. The findings indicate that while most inclusive primary schools in Surakarta offer guidance and counseling services, these services are often limited by factors such as a lack of specialized personnel, inadequate infrastructure, and insufficient time allocation. Additionally, the integration of guidance and counseling services into classroom activities can be challenging due to diverse student needs. To enhance the effectiveness of guidance and counseling services for ABK, it is crucial to provide adequate training for teachers, allocate dedicated time and space for these services, and foster strong collaboration between schools, families, and community organizations.